Prevalence of cervical vertebrae anomalies in patients with cleft lip and palate - Kharbanda Om Prakash; Qureshi Tabassum; Kandasamy Devasenathipathy (Sciendo, 2019)
To investigate the prevalence of cervical vertebral anomalies (CVA) in a group of patients presenting with cleft lip and palate (CLP) and to compare with a non-cleft population.